197 - GUILLAIN-BARRÉ SYNDROME: REVIEW OF LITERATURE (Fiep Bulletin - online, 2011)
GBS is an acute inflammatory demyelinating polyneuropathy of unknown etiology, characterized by flaccid paralysis affecting more than one member, usually symmetrical, with the absence of reflexes and increased liquor protein without pleocytosis. The symptoms are: tingling of the limbs, especially in the lower leg and hands, muscle atonia, decreased reflexes, decreased sensation, uncoordinated movements, muscle pain, blurred vision, difficulty breathing, dizziness, tachycardia, difficulty urination or urinary incontinence, caused by inappropriate secretion of ADH (antidiuretic hormone), constipation, fainting, difficulty swallowing and distal strength deficits. Had as objectives to research, conduct a literature review on the GBS highlighting the clinical and complications that patients develop lifelong disease and to consider conditioning factors and complications to those afflicted with the syndrome. To develop the research, we aimed to publications available in BIREME, (Lilacs / Medline) between the years 1995 to 2008, using the keywords "Guillain Barré Syndrome" and "Guillain Barré and Nursing," from February to April 2008. GBS is a disease of worldwide distribution, occurring virtually independent of the season. It affects any age and there are two peaks of higher incidence (young adults and the elderly), is rare in children under one year old. There is no clear predisposition for the acquisition of this syndrome by gender, but several studies found that men are more frequently affected than women. The annual incidence for the syndrome can reach 8.6 cases per 100,000 inhabitants over 70 years. It is a relatively frequent disease, particularly compared to other neural diseases, being important the knowledge of it and the care of these patients who get ill, aiming to use in their professional practice of the Nursing Systematic Assistance.
Keywords: guillain-barré syndrome; guillain-barré and nursing